The Effect of E-WOM on Social Media Instagram Toward The Decision To Visit Labuan Bajo - Yudhistira, Putu Gde Arie (Journal of Business on Hospitality and Tourism, 2018)
E-WOM is a social media marketing especially on Instagram, which is used to promote a tourist attraction or a product. The purpose of this study was to find out the Effect of E-WOM in Social Media Instagram on the Decision to Visit Labuan Bajo. This research was a descriptive study with a quantitative approach using questionnaire tools for data collection techniques using sample of 100 respondents by taking purposive sampling technique. Respondents used in this research were visitors who had visited Labuan Bajo. This research used 2 variables: Electronic Word of Mouth variable with 5 e-WOM dimensions which were Platform Assistance, Concern for others, Expressing Positive Feeling, Economic Incentive and Helping the Company.Variable Visiting decisions were analyzed using multiple linear regression. The result of percentage of E-WOM in Social Media Instagram on the Decision to Visit Labuan Bajo was 20,6% with two dimensions which had a very strong relationship toward decision to visit, which were dimension Expressing Positive Feeling and Economic Incentive.